Impact of External Debts and FDI Inflows on Export Performance of Nepal: An Application of Gravity Modelling Approach - Paudel, Basundhara; Paudel, Ramesh Chandra (Economic Journal of Nepal, 2023)
As export promotion garners considerable attention from policymakers, export-led growth rapidly becomes the officially proclaimed development plan in many least-developed and developing economies. In recent years, increasingly burdensome external debts, negligible foreign direct investment (FDI) inflows, and poor export performance have become the issue of debate among policymakers. This study uses balanced panel data of Nepal and its top 25 trading partners from 2007 to 2019 to analyze how external debt and FDI inflows affect Nepalese exports employing gravity modeling techniques. The study results show that FDI inflows and external debts positively impact Nepal’s export performance. The study also found that gravity factors, population, and gross domestic product (GDP) of both Nepal and its trading partners had a substantial impact on the exports of the given country. Distance, which acts as a stand-in for transportation costs, has a detrimental effect. The study suggests leveraging debt to finance trade policy and logistics to improve the export-oriented production system and infrastructure development that prioritizes trade and GDP growth.